Modulation-Based Harmonic Elimination - Wells, J.R.; Xin Geng; Chapman, P.L.; Krein, P.T.; Nee, B.M. (IEEE transactions on power electronics, 2007)
A modulation-based method for generating pulse waveforms with selective harmonic elimination is proposed. Harmonic elimination, traditionally digital, is shown to be achievable by comparison of a sine wave with modified triangle carrier. The method can be used to calculate easily and quickly the desired waveform without solution of coupled transcendental equations